Assessing Urban Green Space Accessibility for Sustainable Development in Mostaganem, Algeria: A Space Syntax Approach - Okba Benameur; Fouad Leghrib; Abdelbasset Laroui (Journal of Contemporary Urban Affairs, 2024)
The rapid urbanization of Mostaganem, Algeria, has led to significant challenges in the accessibility of urban green spaces (UGS), crucial for promoting environmental sustainability and public health. This study uses a space syntax approach, specifically angular segment analysis (ASA), to assess UGS accessibility at city-wide and local scales. By integrating quantitative measures like "Choice" and "Integration" with Geographic Information Systems (GIS), the research identifies spatial disparities in green space distribution and accessibility, with global integration values ranging from 0.469 to 0.801. Results reveal unequal distribution, infrastructure inadequacies, and safety issues affecting accessibility. The study highlights areas like Boudjemaa and Emir Abd El Kader, which offer high connectivity, while others like Jannat El Aarif suffer from limited accessibility. Recommendations include enhancing transportation infrastructure, prioritizing green spaces in urban planning, and diversifying facilities to improve accessibility and promote social inclusion. This research provides a comprehensive framework for policymakers and urban planners, aiming to optimize urban green space accessibility and contribute to sustainable urban development in Mostaganem, aligning with global efforts towards equitable urban environments.